Mild hunger elicits attentional desensitization to visual food cues in healthy, non-obese individuals - Schlezingerová, Nicol; Málková, Petra; Kocourek, Martin; Telenský, Petr (Frontiers in Psychology, 2024)
Food is a vital human need, and the human visual system is finely tuned to detect and respond to food ccues in the environment. The omnipresence of food cues across various settings has been linked to the prevalence of obesity in susceptible populations. The influence of the post-prandial state on visual attention to food stimuli remains poorly understood. This study aimed to elucidate how a 12-hour fast affects visual attention to food and non-food stimuli in healthy, non-obese individuals. Visual attention was assessed by measuring the total duration of visual fixations on stimuli presented on a computer screen, using a screen-based eye tracker (Tobii X2-60). Fasted participants exhibited a progressive decline in visual attention towards food stimuli , compared to individuals tested within two hours after consuming breakfast, reflecting a satiated state. Fasted participants exhibited a progressive decline in visual attention towards food stimuli, evidenced by a reduction in the total duration of visual fixations per stimulus. This effect was independent of the palatability of the depicted food items but was not observed with stimuli representing non-food items. Performance on the Food Stroop task revealed no differences between fasting and satiated participants, indicating that the presence of food-related stimuli does not differentially impact attentional interference under varying hunger states. Additionally, no significant variations were observed in electrodermal activity (EDA) responses across participant groups and stimulus types, suggesting that the modulation of visual attention to food cues by hunger is independent of physiological arousal. Interestingly, satiated subjects exhibited higher levels of salivary alpha-amylase, which was inversely related to their subjective hunger ratings. As no differences in salivary cortisol levels were found between groups, this finding implies that salivary alpha-amylase levels may reflect satiety rather than stress. Our data show a novel influence of mild hunger on the processing of visual food cues, independent of physiological arousal.